The reliability and validity of the Turkish version of the telehealth usability questionnaire and the telemedicine satisfaction questionnaire in patients with multiple sclerosis - SARI, ZÜBEYİR (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2021)
Objective: The aim of the study was to translate and cross-culturally adapt the Telehealth Usability Questionnaire (TUQ) and the Telemedicine Satisfaction Questionnaire (TSQ) into Turkish and also to analyze the reliability and validity of both questionnaires. Materials and Methods: A total of 107 multiple sclerosis (MS) patients were recruited. The department clinician monitored all participants with telemedicine for 4 years. Internal consistency was evaluated with Cronbach's alpha coefficient. The test-retest reliability was calculated with intraclass correlation coefficient by analyzing the scores of retested 52 patients 1 week later. The construct validity was examined by Pearson's correlation coefficient (r). Besides, the internal consistency for the subscores of the TUQ and exploratory factor analysis of the TSQ was analyzed. Results: The mean age was 40.5 +/- 11.0 years. Internal consistency of all items and the total score of the TUQ were excellent (>0.80; ranged: 0.976-0.979). On the other hand, the internal consistency of all items and total score of the TSQ was excellent, either (>0.80; ranged: 0.969-0.973). The reproducibility of the total score for the TUQ was excellent (>0.80). The test-retest reliability of all items and the total score of the TSQ were within limits ranging from acceptable to excellent (0.617-0.860). The reliability of the total score for the TSQ was excellent (>0.80). The internal consistency of all subscales of the TUQ was excellent (>0.80). The correlation between TUQ and TSQ was strong (r = 0.882, P < 0.001). The factor loading scores of the TSQ were high (0.814-0.919). Conclusions: The Turkish version of the TUQ and the TSQ are valid and reliable in MS patients.
Keywords: Multiple sclerosis; psychometric properties; Telehealth Usability Questionnaire; Telemedicine Satisfaction Questionnaire; Turkish version; TELEREHABILITATION; ADAPTATION; GUIDELINES